Development and Validation of the Romantic Love Myths Questionnaire - Lara, Laura (Journal of interpersonal violence, 2021)
The purpose of this study was to develop and validate an instrument to measure love myths among Chilean youth. Items created based on review of available literature were refined through experts’ revisions and participant focus groups. The initial questionnaire was applied to 1,538 high school and university students, aged between 14 and 24 years old. Exploratory factor analysis performed with half of the sample led to a 10-item questionnaire, grouped in two factors: idealization and love–abuse. Confirmatory factor analyses conducted with the other half of the sample corroborated this factorial structure. Reliability analyses indicated an adequate internal consistency, and correlations with dating violence and quality of relationship provide evidence on its concurrent validity. Complementary, results showed that females endorse more idealization and males love–abuse, and adolescents scored higher in both dimensions than emerging adults.